2013
DOI: 10.1111/ppl.12097
|View full text |Cite
|
Sign up to set email alerts
|

Cell and tissue dynamics of olive endocarp sclerification vary according to water availability

Abstract: Endocarp developmental timing in drupe-type fruits, involving tissue expansion and sclerification processes, is increasingly used as marker for biological studies and crop management. In spite of its wide application, however, little is known regarding how these morphogenetic processes unfold or the factors that modify it. This study evaluates endocarp expansion and sclerification of olive (Olea europaea) fruits, used as an example of drupe-type fruits, from trees growing under different water regimes: full ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 54 publications
(106 reference statements)
1
14
0
1
Order By: Relevance
“…The effect of water availability on endocarp development was further investigated by Hammami et al (2013). Maximum mesocarp-to-endocarp ratio is an important feature for olive fruit quality for both table consumption and oil production.…”
Section: Fruit Developmentmentioning
confidence: 99%
“…The effect of water availability on endocarp development was further investigated by Hammami et al (2013). Maximum mesocarp-to-endocarp ratio is an important feature for olive fruit quality for both table consumption and oil production.…”
Section: Fruit Developmentmentioning
confidence: 99%
“…This phenological stage is a dynamic period which can change in length with the water status of the tree (Hammani et al, 2013). In addition, in conditions of significant fruit load in the tree, vegetative growth is stopped (Rallo and Suarez, 1989) and water relations are clearly changed in comparison with low fruit load conditions (Martin-Vertedor et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hammami et al () also showed that the fruits of trees under rainfed treatment delayed pit hardening at 12 weeks AFB, although other studies on the development of the pericarp of the olive locate the end of the endocarp sclerification between 4 and 6 weeks AFB (Lavee, ), between 7 and 9 weeks AFB (Rallo & Cuevas, ) and between 8 and 10 weeks AFB (Rapoport et al, ). This variability in the stage where the sclerification of the endocarp is reached and the lack of coincidence with what was observed in this work could be due to the different varieties of olive, to the crop growing conditions, such as water status (Hammami et al, ), to the frequency with which the samples were taken or the different ways of measuring the hardness or to the possible variation between the sclerification and the hardness.…”
Section: Resultsmentioning
confidence: 97%
“…In the olive fruit, this process occurs in the cells of the endocarp and is responsible for its hardening as in other drupes (Gómez del Campo & Rapoport, ; Roth, ). The sclerification of endocarp occurs gradually during the growth of the fruit, beginning a few days AFB and ending between 10 and 11 weeks AFB (Hammami, Costagli, & Rapoport, ; Rallo‐Morillo & Rapoport, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation